The use of Extended Petri Nets in Analyzing the Reliability of MV / LV Distribution Transformer Stations - Chojnacki, A. L. (Elektronika ir Elektrotechnika, 2012)
The article presents the results of a verification of the suitability of a method based on extended Petri nets to determine the indicators as well as the reliability characteristics of power stations. The author presented the theoretical basis of extended Petri nets. He conducted simulation of a station failure, using a program based on the rules of a Petri net, and a reliability analysis based on empirical data from service stations. He made a comparison of the coefficients and the properties of reliability obtained by both methods , yielding similar results. Based on the analysis, the author concluded that Petri nets are a very convenient and accurate tool to perform reliability analysis of complex power systems. Ill. 8, bibl. 9, tabl. 2 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.121.5.1645